New Evidence on the Impacts of Early Exposure to the 1918 Influenza Pandemic on Old-Age Mortality: A Research Note - Jason M. Fletcher (Institute of Labor Economics (IZA), 2018)
This paper provides new evidence of the impacts of early life exposure to the 1918 pandemic on old-age mortality by analyzing data from the National Longitudinal Mortality Study (n ~ 220,000). The specifications used year and quarter of birth indicators to assess the effects of timing of pandemic exposure and used Cox proportional hazard models for all-cause mortality outcomes. The findings suggest evidence of excess all-cause mortality for cohorts born during 1918 and mixed evidence for cohorts born in 1917 and 1919. Therefore, contrary to some existing research, the results suggest no consistent evidence of the importance of specific windows of exposure by gestation period.
Keywords: I14; 330; early conditions; in utero; 1918 influenza pandemic; mortality